Osteoporose associada à gestação/lactação : análise histomorfométrica e resposta ao tratamento com ácido zoledrônico - Grizzo, Felipe Merchan Ferraz (2015)
Pregnancy and lactation-associated osteoporosis is a rare condition with little known pathophysiology. Most cases are diagnosed in the third trimester of pregnancy or in the first weeks postpartum, particularly in first pregnancies. Vertebral fractures are most commonly observed and characterized by prolonged severe pain, functional limitations and a loss of height. Measurements of bone mineral density and biochemical markers of bone remodelling are the clinical methods most commonly used for the management of these patients. However, a bone biopsy with histomorphometric analysis has been considered to be the gold-standard. Few studies have evaluated the histomorphometry in patients with this clinical condition and none of them performed the procedure at the beginning of the clinical assessment. In this study, we report a case of pregnancy and lactation-associated osteoporosis in a 31 years old postpartum patient who had undergone a twin pregnancy. We describe the clinical, laboratory tests and imaging features. Bone histomorphometry showed a high resorption rate and excellent evolution after 1 year of treatment with intravenous zoledronic acid. Our data suggest that osteoclastogenesis plays a central role in the pathophysiological processes of this disease.